PATTERN OF SNAKE BITE CASES VISITING AT RURAL HEALTH CENTRE OF SINDH, PAKISTAN: Pattern of Snake Bite Cases in Sindh Pakistan - Agha, Dr Sajida; Shahani, Rukhsar; Farsi Kazi, Salman Ahmed (Pakistan Armed Forces Medical Journal, 2010)
Objective: This study was carried out to determine the pattern of snake bite in a rural area of Sindh Pakistan over a 07-year period.Study Design: A Descriptive StudyPlace and Duration of Study: A total record of 5737 snake bite cases attending rural health centre Ranipur District Khairpur between 2000 and 2007 were analysed retrospectively.Patients and Method: A retrospective review of record of snake bite patients was carried out who had attended the health care centre first time for further management. Patients with history of previous visit for treatment were excluded from the study.Results: Out of 5737 victims 44.18% were children less than 15 years and 22% were more than 35 years. Most of the patients (87.22%) were hospitalized after 24 hours of the snake bite. Majority of them (91.99%) came with the history of single bite. Of the 5337 envenomed by poisonous snakes, 56.99% were bitten by Cobra, and 35% by Krait and Viper. Lower extremities were the most common sites of the snake bite (69.99%).Conclusion: Snake bite is one of a significant problem in the study area. We observed the delayed consultation of the victims to the hospital. Further research on successful management of these victims was recommended.